Death Penalty in Indonesia - Salam, Abdul Jalil; Karim, Zahlul Pasha (University of Jember, 2021)
Historically, Indonesia's death penalty does not originate from religious doctrine but a series of democratization processes agreed upon in the legislation. Amidst these processes, two competing opinions respond to Indonesia's death penalty: the retentionist and the abolitionist. These different approaches to address the death penalty, whether imposed or abolished, result in competing perspectives and arguments in regulatory and practical issues both in the national and international arena. This study aimed to revisit the death penalty discourse in Indonesia that opposes the human approach by assuming that the death penalty violates human rights. The data were analyzed in three steps, among other things, unitization, comparison, and conclusion. This study showed that the death penalty remains relevant to Indonesia despite the long struggle of its rejection. It concluded that Indonesia's imposition of the death penalty is regarded as worth defending, with specific and selective applications. The specific application means that the death penalty is applicable for corruptors, drug dealers, terrorists, gross human rights violators, and premeditated murders. Selective application means that a convict sentenced to death must be proven in court with a level of accuracy considered and accepted in law. KEYWORDS: Death Penalty, Criminal Law, Right to Life, Indonesian Law.